(407) Problems of Accelerated Growth مشكلات النمو المتسارع - Hosny, A (معهد التخطيط القومى, 2024)
The study entitled “Problems of Accelerated Growth” examines economic issues associated with achieving high rates of economic growth, particularly in developing countries seeking to transition from traditional economic structures toward modern and sustainable development systems. The significance of the study lies in the argument that accelerated economic growth is not solely determined by increasing investment rates or expanding production capacity, but also by structural, institutional, and human factors that directly influence the effectiveness of development policies. The study aims to analyze the challenges faced by economies pursuing rapid growth, with particular emphasis on the relationship between economic planning, resource allocation, and manpower development. It further seeks to explain the role of economic policies in directing investment toward sectors capable of generating higher productive returns and supporting structural transformation processes. The research adopts an analytical framework based on theories of economic growth and development planning, emphasizing the importance of capital accumulation, technological progress, and improvements in labor productivity in sustaining long-term economic growth. The study also discusses challenges associated with limited resources, institutional weaknesses, sectoral imbalances, and deficiencies in workforce skills and human resource development. The findings suggest that accelerated growth requires integration between economic, social, and educational policies and that reliance on capital expansion alone may not be sufficient to ensure sustainable growth. The analysis further highlights the importance of investing in human capital and strengthening planning mechanisms to improve the efficient allocation of available resources. The study contributes by providing a conceptual framework that assists researchers and policymakers in understanding the nature of constraints affecting rapid growth strategies and offers analytical foundations for designing more effective and sustainable development policies.